A comprehensive appraisal of mechanism of anti-CRISPR proteins: an advanced genome editor to amend the CRISPR gene editing - Choudhary, Nisha; Tandi, Dipty; Verma, Rakesh Kumar; Yadav, Virendra Kumar; Dhingra, Naveen; Ghosh, Tathagata; Choudhary, Mahima; Gaur, Rajarshi K.; Abdellatif, Magda H.; Gacem, Amel; Eltayeb, Lienda Bashier; Alqahtani, Mohammed S.; et al. (Frontiers in Plant Science, 2023)
The development of precise and controlled CRISPR-Cas tools has been made possible by the discovery of protein inhibitors of CRISPR-Cas systems, called anti-CRISPRs (Acrs). The Acr protein has the ability to control off-targeted mutations and impede Cas protein–editing operations. Acr can help with selective breeding, which could help plants and animals improve their valuable features. In this review, the Acr protein–based inhibitory mechanisms that have been adopted by several Acrs, such as (a) the interruption of CRISPR-Cas complex assembly, (b) interference with target DNA binding, (c) blocking of target DNA/RNA cleavage, and (d) enzymatic modification or degradation of signalling molecules, were discussed. In addition, this review emphasizes the applications of Acr proteins in the plant research.